2016
DOI: 10.2480/agrmet.d-14-00016
|View full text |Cite
|
Sign up to set email alerts
|

The photosynthetic response of four seral deciduous broad-leaved tree seedlings grown under elevated CO<sub>2</sub> concentrations

Abstract: To test the relationship between successional traits and photosynthetic response to elevated CO 2 , we evaluated the photosynthetic and biochemical traits in the leaves of four deciduous broad-leaved tree species with different successional traits grown under ambient (370 µmol mol -1 ) and elevated (720 µmol mol -1 ) CO 2 concentrations (CO 2 ). All four seedlings showed photosynthetic downward regulation, which is characterized by successional type-specific differences. In the mid-successional tree species, M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 46 publications
0
7
0
Order By: Relevance
“…some under manipulated conditions (Toledo-Aceves, López-Barrera and Vásquez-Reyes, 2017), others in common garden experiments whilst yet others are gathered in the wild). Other studies in this literature present findings from trait studies but not the data themselves, making them impossible to interrogate or contextualise (Kitaoka et al, 2016;Oguchi, Hiura and Hikosaka, 2017). Attempts to explain trait coordination through strategies or Plant Functional Types are highly attractive and hold great promise for specification in urban forestry but at the time of writing, remain elusive: conceptually elegant schemes such as the Fast Slow Spectrum (Reich, 2014) or the CSR triangle (Pierce et al, 2017) rely upon proxy traits to too great an extent at present to explain functional trait coordination within woody plants.…”
Section: Clear Differences Between Literature Sourcesmentioning
confidence: 99%
“…some under manipulated conditions (Toledo-Aceves, López-Barrera and Vásquez-Reyes, 2017), others in common garden experiments whilst yet others are gathered in the wild). Other studies in this literature present findings from trait studies but not the data themselves, making them impossible to interrogate or contextualise (Kitaoka et al, 2016;Oguchi, Hiura and Hikosaka, 2017). Attempts to explain trait coordination through strategies or Plant Functional Types are highly attractive and hold great promise for specification in urban forestry but at the time of writing, remain elusive: conceptually elegant schemes such as the Fast Slow Spectrum (Reich, 2014) or the CSR triangle (Pierce et al, 2017) rely upon proxy traits to too great an extent at present to explain functional trait coordination within woody plants.…”
Section: Clear Differences Between Literature Sourcesmentioning
confidence: 99%
“…2c), indicating that large amounts of starch diluted the leaf N (Gifford et al, 2000), specifically for hardwood rather than conifer species. Some studies that reported a decrease in the N area have claimed that down-regulation of photosynthesis was due to the dilution effect (Gutierrez et al, 2013;Kitaoka et al, 2016), but, as defined in the introduction of the present study, it should be attributed to N limitation rather than dilution. In the present study, there was a decrease in N mass with no differences in the N area among treatments (Fig.…”
Section: Dilution Effects and Down-regulation Of Photosynthesismentioning
confidence: 59%
“…Without sufficient N, plants cannot maintain their initial enhanced C uptake, due to the N-driven down-regulation of photosynthesis after long-term CO 2 exposure (Norby et al, 2010). Alternatively, the dilution effect caused by the excessive accumulation of nonstructural carbohydrates (NSC), which results in reduced N mass under CO 2 enrichment conditions, is another commonly considered hypothesis (Kitaoka et al, 2016;Rogers & Ellsworth, 2002). However, we propose that the dilution effect should not be confused with a reduction in N area because a decrease in N area under eCO 2 is commonly attributed to a reduction in the rate of N uptake (McDonald, Erickson, & Kruger, 2002) or the availability of N (Norby et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…This stimulating effect of photosynthesis caused by elevated levels of CO 2 may be temporary, given the acclimation of photosynthesis to elevated concentrations of CO 2 , which initially stimulates the fixation of C but is followed by a slow decrease in the C fixation process [42]. Various studies have indicated that the acclimation of photosynthesis is due to factors such as reduced content of Rubisco [43], the inhibition of the assimilation of C due to the accumulation of non-structural carbohydrates that suppress the expression of genes related to photosynthesis [43,44], and a reduction in the concentration of nutrients, especially N in plant tissues, due to the inhibition of photoassimilates of NO 3 − [45 -47]. In Populus tremuloides and B. papyrifera in the presence of elevated CO 2 , net photosynthesis in-creased by 43-73% and the hexose ratio increased when compared with that of sucrose [48].…”
Section: Elevated Co 2 Levels and Elevated Temperatures On Carbon Metabolism In Sunflower Plantsmentioning
confidence: 99%